GAMBARAN INISIASI MENYUSU DINI (IMD) TERHADAP LAMA KALA III PADA IBU BERSALIN DI RUANG MINA RS MUHAMMADIYAH TUBAN - Qonitun, Umu; Aini, Ida Nur (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACTPlacental exposure is part of the third stage of active management in labor, if in the third stage is not normal or placenta difficult to detach it will result in retention of the placenta and the occurrence of bleeding. Effective uterine contractions will accelerate placental exertion, prevent bleeding, and reduce blood loss. Factors that affect the length of placental expenditure one of them is Early Breastfeeding Initiation. Maternal mortality (MMR) in Indonesia is still high at 309 per 100,000 live births (SDKI 2007). In 2013 the cause of maternal mortality in Indonesia due to retention of placenta as much (30.3%) (Ministry of Health RI, 2016). While at Muhammadiyah Hospital Tuban in january - juni Year 2017 The number of bleeding events is (9) people. The purpose of this research is to know the implementation of Early Breastfeeding Initiation on the third stage of maternal womb in the Mina Room of Tuban Muhammadiyah Hospital.The research method using descriptive method, Population of research is all mother maternity in RS Muhammadiyah Tuban which amounts to 29 mother maternity. Sampling technique using purposive sampling with number of 29 maternal mothers who meet the inclusion criteria of maternity mother with normal delivery, maternity mother who is willing to be a research respondent, and healthy babies. Collecting data using direct observation in collaboration at RS Muhammadiyah Tuban.The results of this study are mostly maternal mothers who are in accordance with all the procedures of IMD (93.1) while the maternal mother with normal third stage is (93.1). So it is concluded that there is influence of Early Breastfeeding Initiation on the duration of placental expenditure in the third stage of delivery at Muhammadiyah Hospital Tuban.The conclusion of this research is the influence of early breastfeeding Initiation on the duration of placental expenditure in the third stage of labor. It is expected that patients get real information about the effect of Early Breastfeeding Initiation, as well as for Tuban Muhammadiyah Hospital especially in Minor Room, expected to improve the implementation of IMD implementation in accordance with established procedures. Keywords: early breastfeeding initiation, stage III